Experimental Study on Heat Loss of a Single Screw Expander for an Organic Rankine Cycle System - Wang, Wei; Shen, Li-li; Chen, Ru-meng; Wu, Yu-ting; Ma, Chong-fang (Frontiers in Energy Research, 2020)
For displacement expanders, the irreversible losses include leakage, friction, heat dissipation, and flow resistance. Currently, the research on the heat loss of expanders is scarce, especially with regards to experimental studies. In this paper, the experimental research on the heat loss of the single screw expander (SSE) for the Organic Rankine Cycle was carried out under different working conditions, in the summer and winter, respectively. In each set of experiments, there were five cases, and the temperatures of the working fluids at the inlet of the expander were 83 ℃, 93 ℃, 103 ℃, 113 ℃, and 123 ℃, respectively. The heat removed by the lubricating oil was also measured throughout the experimental period. The experimental results showed that the amount of heat loss was not comparable to the output power and enthalpy difference between the inlet and outlet of the SSE. The proportion of the heat dissipated by the casing was only 30% ranging from 0.11-0.28 kW. Comparing the experimental results in summer and winter, the heat loss in summer was lower than in winter, but the variation in output power showed an opposite trend. It was also shown that heat loss was not a main factor affecting the performance of SSEs.